The Influence of the Agricultural Sector on Poverty Levels in Rural Areas of North Sumatra 2015-2024 - Ginting, Renata Olivia; Novita Sari Br Kaban; Hernita Siagian; Desry Rasmita Tarigan; Muammar Rinaldi (Outline Publisher, 2025)
This study aims to analyze the influence of the agricultural sector on poverty rates in rural areas of North Sumatra during the period 2015–2024. The background of this study is based on the fact that most rural residents depend on the agricultural sector for their livelihoods, but the poverty rate is still relatively high. This study uses a quantitative approach with secondary data from the Central Statistics Agency (BPS) and simple linear regression analysis using SPSS version 2022. The results of the study show that the agricultural sector has a significant effect on poverty rates, as indicated by the significance value of the T test and F test of 0.009 (<0.05). A negative regression coefficient of -0.022 indicates an inverse relationship, namely that an increase in the contribution of the agricultural sector tends to reduce poverty rates. The R² value of 0.599 indicates that 59.9% of the variation in poverty rates is explained by the agricultural sector, while the remaining 40.1% is influenced by other factors. This study concludes that strengthening the agricultural sector through increased productivity, access to technology, and sustainable policy support is an important strategy in reducing poverty in rural areas of North Sumatra.